High-toughness lightweight multi-component refractory green alloy and preparation method thereof

By recycling titanium, niobium and zirconium alloys, using multi-component alloy design and specific preparation processes, a high-strength, tough, lightweight multi-component refractory green alloy was developed, solving the problems of refractory metals in processing and application, and achieving a combination of high performance and low cost.

CN119663088AActive Publication Date: 2025-03-21CENT SOUTH UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411857124.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The mining and processing of existing refractory metals is difficult, the raw materials are expensive, the density is high, the room temperature plasticity and the difficulty of deformation processing are limited, which limits its application in aerospace, military equipment and other fields.

Method used

By recycling titanium alloys, niobium alloys and zirconium alloys, using the multi-component alloy design idea, a high-strength, tough and lightweight multi-component refractory green alloy was developed, and prepared by vacuum arc smelting, cold rolling deformation and vacuum or inert gas annealing processes.

Benefits of technology

The preparation of high-strength, tough, lightweight multi-component refractory green alloy is realized, with good room temperature tensile elongation and yield strength, simplifying the preparation process and reducing costs, alleviating resource tightness and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663088A_ABST
    Figure CN119663088A_ABST
Patent Text Reader

Abstract

The invention discloses a high strength and toughness light multi-component refractory green alloy and a preparation method thereof, the multi-component high strength and toughness refractory green alloy is obtained by smelting raw materials of recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy, and the multi-component high strength and toughness refractory green alloy comprises the following components in percentage by mass: 28-55 wt% of recycled titanium alloy, 22-35 wt% of recycled niobium alloy and 22-38 wt% of recycled zirconium alloy. Compared with the currently developed refractory alloy, the high-strength-toughness light-weight multi-component refractory green alloy prepared by the preparation method disclosed by the invention has the advantages of lower mass density, better strength and toughness matching and shorter preparation process flow, and can be applied to the fields of aerospace, nuclear energy industry, chemical industry and the like; and meanwhile, the recycled alloy is upgraded and utilized, so that the problem of resource shortage can be effectively relieved, the production cost is reduced, and the development of circular economy is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal materials and preparation thereof, and specifically relates to a high-strength, light-weight, multi-component refractory green alloy and a preparation method thereof. Background Art

[0002] Every year, the world produces and consumes a large amount of metal materials, generating a huge amount of metal waste, which places a heavy burden on resources, energy and the environment. Secondary synthesis is currently the main method for recycling metal waste to reduce the cost of alloy preparation and reduce the burden on resources, energy and the environment. However, the performance of secondary synthetic alloys is very limited and single, usually similar to or even lower than the original alloy, and most secondary synthetic alloys are downgraded or used at the same level. As a result, the application of recycled alloys has many limitations. Therefore, if high-strength and tough green alloys can be developed, it will be of great significance to reduce the cost of alloy preparation, expand the application field of recycled alloys, and develop a green and low-carbon economy.

[0003] The new generation of high-performance structural materials requires lightweight and excellent strength and toughness matching. Traditional structural materials are often based on one or two metals, and it is difficult to achieve multiple excellent properties at the same time. As an innovative alloy design concept, multi-component alloys break through the scope of traditional alloy design, which provides the possibility of exploring ideal performance in a wide range of combination spaces. Multi-component refractory alloys play an important role in modern industry with their excellent high-temperature performance and excellent corrosion resistance. This type of alloy is mainly composed of refractory metal elements such as Nb, Zr, V, and Ti, and is widely used in aerospace, military equipment, nuclear industry, chemical industry and other fields; at the same time, a large number of "retired" alloys are also produced, with huge output; and refractory metal resources are unevenly distributed, and mining and processing are difficult, resulting in expensive raw materials and a large amount of pollutants in the production process, which has a serious impact on the environment. Therefore, how to develop low-cost green refractory alloys and improve their processing deformation capabilities has always been a core issue that needs to be solved urgently. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above-mentioned and / or existing problems in the prior art, such as the difficulty in mining and processing of existing refractory metals, expensive raw materials, high density, poor room temperature plasticity and difficulty in deformation processing, the present invention is proposed.

[0006] One of the purposes of the present invention is to provide a high-strength, tough, lightweight, multi-component refractory green alloy, to provide a high-strength, tough, lightweight, multi-component refractory green alloy and a preparation method thereof, aiming to develop a low-cost, green multi-component refractory alloy to solve its problems such as poor room temperature plasticity and poor deformability.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength and toughness, lightweight, multi-component refractory green alloy, a high-strength and toughness, lightweight, multi-component refractory green alloy, characterized in that:

[0008] The green alloy is obtained by smelting recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy as raw materials, wherein, by weight percentage, the recycled titanium alloy is 28-55wt%, the recycled niobium alloy is 22-35wt%, and the recycled zirconium alloy is 22-38wt%.

[0009] Among them, the recycled titanium alloy is Ti6Al4V alloy, the recycled niobium alloy is Nb-1Zr alloy, and the recycled zirconium alloy is Zr-2.5Nb alloy.

[0010] As a preferred solution of the high-strength, toughness, lightweight, multi-component refractory green alloy of the present invention, the recycled titanium alloy is Ti6Al4V alloy, including Ti6Al4V alloy derived from waste oil drilling drill pipes, valves, pump bodies, eyeglass frames, bicycle frames, and mobile phone casings.

[0011] As a preferred solution of the high-strength, toughness, lightweight, multi-component refractory green alloy of the present invention, the recycled niobium alloy is a Nb-1Zr alloy, including Nb-1Zr alloys derived from waste high-temperature material nozzles, waste nuclear reactor cladding materials, and waste surgical tools.

[0012] As a preferred solution of the high-strength, toughness, lightweight, multi-component refractory green alloy of the present invention, the recycled zirconium alloy is a Zr-2.5Nb alloy, including Zr-2.5Nb alloys derived from waste electronic device circuit board brackets, waste kitchen knives, waste nuclear reactor cladding materials, and waste nuclear industrial materials.

[0013] As a preferred embodiment of the high-strength, toughness, lightweight, multi-component refractory green alloy of the present invention, the green alloy comprises, by atomic percentage, 38.0-60.0 at% Ti, 14-28.0 at% Zr, 14.0-28.0 at% Nb, 4.0-8.0 at% Al, 1.0-4.0 at% V and trace elements Fe, Ta, W, Si, Ni, Mo and Cr, and the atomic percentage of each trace element is 0.01-2.0 at%.

[0014] As a preferred embodiment of the high-strength and toughness light-weight multi-component refractory green alloy of the present invention, the high-strength and toughness light-weight multi-component refractory green alloy has the following characteristics:

[0015] (a) The density of the alloy is 5.30-6.00 g / cm 3 ;

[0016] (b) Direct cold rolling-annealing treatment can be achieved at room temperature, with a cold rolling deformation of 20 to 100%;

[0017] (c) The tensile yield strength of the high-strength, lightweight, multi-component refractory green alloy at room temperature is 800-1100 MPa;

[0018] (d) The tensile elongation of the high-strength, tough, lightweight, multi-component refractory green alloy at room temperature is greater than 30.0%; specifically, greater than 35%; further, greater than 37%; and optimally, greater than 38.55%.

[0019] Another object of the present invention is to provide a method for preparing the high-strength, tough, lightweight, multi-component refractory green alloy as described above, comprising:

[0020] Recover titanium alloy, niobium alloy and zirconium alloy raw materials according to mass ratio;

[0021] Use vacuum arc melting or vacuum induction melting;

[0022] By cold rolling deformation and then annealing in vacuum or protective atmosphere, a high-strength, tough, lightweight, multi-component refractory green alloy is obtained.

[0023] As a preferred embodiment of the method for preparing the high-strength, tough, lightweight, multi-component refractory green alloy of the present invention, the smelting is carried out in a vacuum or inert gas atmosphere; the smelting under vacuum has a vacuum degree of ≥1×10 -1 Pa; the smelting is carried out under an inert gas atmosphere, and the inert gas pressure in the smelting furnace is 0.000001~0.05MPa.

[0024] As a preferred solution of the method for preparing the high-strength, toughness, lightweight, multi-component refractory green alloy of the present invention, wherein: the cold rolling deformation is adopted, the single-pass rolling reduction is ≤20%, and the total rolling reduction is 20% to 100%.

[0025] As a preferred embodiment of the method for preparing the high-strength, tough, lightweight, multi-component refractory green alloy of the present invention, annealing is performed in a vacuum or inert gas atmosphere at a temperature of 700 to 1250°C for 5 to 60 minutes, followed by quenching; annealing may also be further followed by aging treatment at a temperature of 100 to 600°C for 0 to 800 hours, followed by quenching as required.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention introduces a multi-component alloy design concept, and develops a multi-component refractory green alloy with high strength and toughness by recycling titanium alloy, recycling niobium alloy and recycling zirconium alloy, which can not only simplify the cumbersome preparation process, but also reduce the preparation cost. Using recycled alloys instead of pure metals as raw materials for preparing high-strength and tough refractory alloys can effectively alleviate the problem of resource shortage to reduce production costs, reduce the exploitation of mineral resources to reduce environmental pollution, and help promote the development of the circular economy and achieve sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0029] Figure 1 For Example 1Ti 44.76 Zr 25.68 Nb 22.39 Al 5.3 V 1.87 Scanning electron microscope microstructure of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0030] Figure 2 For Example 1Ti 44.76 Zr 25.68 Nb 22.39 Al 5.3 V 1.87 XRD spectrum of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment by cold rolling.

[0031] Figure 3 For Example 1Ti 44.76 Zr 25.68 Nb 22.39 Al 5.3 V 1.87 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0032] Figure 4 For Example 1Ti 44.76 Zr 25.68 Nb 22.39 Al 5.3 V 1.87 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after aging treatment.

[0033] Figure 5 For Example 2Ti 49.34 Zr 21.25 Nb 21.51 Al 5.84 V 2.06 Scanning electron microscope microstructure of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0034] Figure 6 For Example 2Ti 49.34 Zr 21.25 Nb 21.51 Al 5.84 V 2.06 XRD spectrum of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment by cold rolling.

[0035] Figure 7 For Example 2Ti 49.34 Zr 21.25 Nb 21.51 Al 5.84 V 2.06 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0036] Figure 8 For Example 2Ti 49.34 Zr 21.25 Nb 21.51 Al 5.84 V 2.06 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after aging treatment.

[0037] Fig. 9 Example 3Ti 53.60 Zr 17.14 Nb 20.68 Al 6.34 V 2.24 Scanning electron microscope microstructure of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0038] Fig.10 Example 3Ti 53.60 Zr 17.14 Nb 20.68 Al 6.34 V 2.24 XRD spectrum of high-strength, tough, lightweight multi-component refractory green alloy after 90% homogenization treatment by cold rolling.

[0039] Fig.11 Example 3Ti 53.60 Zr 17.14 Nb 20.68 Al 6.34 V2.24 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0040] Fig.12 Example 3Ti 53.60 Zr 17.14 Nb 20.68 Al 6.34 V 2.24 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after aging treatment.

[0041] Fig.13 For Example 4Ti 57.54 Zr 16.53 Nb 16.72 Al 6.81 V 2.40 Scanning electron microscope microstructure of high-strength, tough, lightweight multi-component refractory green alloy after 80% homogenization treatment by cold rolling.

[0042] Fig.14 For Example 4Ti 57.54 Zr 16.53 Nb 16.72 Al 6.81 V 2.40 XRD spectrum of high-strength, tough, lightweight, multi-component refractory green alloy after 80% homogenization treatment by cold rolling.

[0043] Fig.15 For Example 4Ti 57.54 Zr 16.53 Nb 16.72 Al 6.81 V 2.40 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after 90% homogenization treatment of cold rolling.

[0044] Fig.16 For Example 4Ti 57.54 Zr 16.53 Nb 16.72 Al 6.81 V 2.40 Tensile engineering stress-engineering strain curve of high-strength and toughness lightweight multi-component refractory green alloy after aging treatment.

[0045] Fig.17 This is a physical picture of the alloy of comparative example 4 during the rolling deformation process. DETAILED DESCRIPTION

[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0047] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0048] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0049] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0050] The recycled titanium alloy used in the embodiment of the present invention is Ti6Al4V alloy from waste oil drilling drill pipes; the recycled niobium alloy is Nb-1Zr alloy from waste surgical tools; and the recycled zirconium alloy is Zr-2.5Nb alloy from waste electronic device circuit board brackets.

[0051] The test method used in the embodiment of the present invention is:

[0052] Tensile test: The sample obtained in the example was cut into dog-bone tensile specimens of 1.62×7.5×21 mm by wire cutting, and polished on 180#, 400#, 800#, 1200#, 2000#, 3000#, and 5000# sandpaper. The polished sample was ultrasonically cleaned for 20 min and dried. -3 s -1 Stretching was performed at a strain rate of .

[0053] Density determination: measured by Archimedes drainage method, firstly, the as-cast sample obtained in the embodiment is uniformly cut into 8×8×8 mm block samples, used before measurement, ultrasonically cleaned at room temperature for 20 minutes to remove surface dirt and impurities, and finally placed in a drying oven for drying; weigh the dry weight M1 of each sample, and weigh each sample 6 times to reduce the measurement error; then weigh the mass M2 of each sample in water, and weigh each sample 6 times; finally, calculate the density according to the following formula:

[0054]

[0055] Where ρ0 is the temperature of water, 0.9982 g / cm 3 (293K); ρ1 is the air density, 0.0012g / cm 3 , measure three times and get the average value.

[0056] Example 1

[0057] (1) Raw material pretreatment: The recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy were polished and ultrasonically cleaned at room temperature for 30 minutes to remove surface dirt and impurities, and finally placed in a drying oven for drying;

[0058] (2) Raw material ratio: According to the chemical formula Ti 44.76 Zr 25.68 Nb 22.39 Al 5.3 V 1.87 The molar percentage and mass percentage of (atomic percentage) are converted, and the ingredients are prepared based on 100g of alloy according to the recycled alloy mass ratio Ti6Al4V:Zr-2.5Nb:Nb-1Zr=35:35:30;

[0059] (3) Melting: The raw materials weighed in step (2) were placed into a water-cooled copper crucible in a vacuum arc furnace according to their melting points, and the vacuum was evacuated to 5×10 -3 Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 2 minutes to consume the residual oxygen and nitrogen in the smelting furnace, the smelting current is 340A, and the smelting time is 180 seconds; start smelting the alloy ingot, smelting repeatedly 8 times, the smelting current is controlled at 400A, each smelting arc should last for 8 minutes and supplemented with electromagnetic stirring technology, the current frequency is 10Hz, to ensure that the alloy is fully mixed;

[0060] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample is cooled, the sample is taken out. The specific operation is as follows: vacuumize to 4×10 -3 Pa, repeated three times; filled with argon to 0.04MPa as a protective atmosphere; melted the extra Ti ingots pre-placed in the furnace before smelting, the smelting current was 340A, and the smelting time was 120 seconds; began to smelt the alloy ingot, repeated smelting 4 times, the smelting current was controlled at 400A, and each smelting arc should last for 8min;

[0061] (5) Cold rolling annealing: The cast alloy was cut into 10.00 mm thick strip-shaped samples, with a single-pass rolling reduction of 10% and a total rolling reduction of 90%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first evacuated to 1×10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.001MPa. After the sealing is completed, the sample is kept at 850℃ for 10min and then immediately quenched in water to obtain a high-strength, lightweight, multi-component refractory green alloy. The density is measured by the Archimedes drainage method, ρ = 5.928g / cm 3 .

[0062] Figure 1 This is a scanning electron microscope micrograph of the high-strength and light-weight multi-component refractory green alloy of Example 1 after cold rolling and annealing for 90%. It can be seen that the multi-component refractory green alloy can be subjected to large deformation microstructure control in the cast state. After annealing, the alloy microstructure is dense and the grain size is evenly distributed. Statistics show that the grain size is 10.12±2.34μm.

[0063] Figure 2 is the corresponding XRD pattern of Example 1;

[0064] Figure 3 This is a tensile engineering stress-engineering strain curve of the high-strength and toughness lightweight multi-component refractory green alloy of Example 1 after 90% homogenization treatment by cold rolling. The alloy has a yield strength of 976 MPa and a tensile elongation of 38.55% at room temperature.

[0065] The obtained high-strength, tough, lightweight, multi-component refractory green alloy was further aged at a temperature of 350°C for 168 h, followed by immediate water quenching. Figure 4 This is a tensile engineering stress-engineering strain curve of the high-strength and toughness lightweight multi-component refractory green alloy in Example 1 after annealing and further aging treatment. The strength is significantly improved after aging treatment.

[0066] Example 2

[0067] (1) Raw material pretreatment: The recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy were polished and ultrasonically cleaned at room temperature for 30 minutes to remove surface dirt and impurities, and finally placed in a drying oven for drying;

[0068] (2) Raw material ratio: According to the chemical formula Ti 49.34 Zr 21.25 Nb 21.51 Al 5.84 V 2.06 The molar percentage and mass percentage of (atomic percentage) are converted based on 100g of alloy, and the ingredients are prepared according to the recycled alloy mass ratio Ti6Al4V:Zr-2.5Nb:Nb-1Zr=40:30:30;

[0069] (3) Melting: The raw materials weighed in step 2 were placed into a water-cooled copper crucible in a vacuum arc furnace in order of their melting points, and the vacuum was evacuated to 5 × 10 -3Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 2 minutes to consume the residual oxygen and nitrogen in the smelting furnace, the smelting current is 340A, and the smelting time is 180 seconds; start smelting the alloy ingot, smelting repeatedly 8 times, the smelting current is controlled at 400A, each smelting arc should last for 8 minutes and supplemented with electromagnetic stirring technology, the current frequency is 10Hz, to ensure that the alloy is fully mixed;

[0070] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample is cooled, the sample is taken out. The specific operation is as follows: vacuumize to 4×10 -3 Pa, repeated three times; filled with argon to 0.04MPa as a protective atmosphere; melted the extra Ti ingots pre-placed in the furnace before smelting, the smelting current was 340A, and the smelting time was 120 seconds; began to smelt the alloy ingot, repeated smelting 4 times, the smelting current was controlled at 400A, and each smelting arc should last for 8min;

[0071] (5) Cold rolling annealing: The cast alloy was cut into 10.00 mm thick strip-shaped samples, with a single-pass rolling reduction of 10% and a total rolling reduction of 90%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first evacuated to 1×10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.001MPa. After the sealing is completed, the sample is kept at 850℃ for 10min and then immediately quenched in water to obtain a high-strength, lightweight, multi-component refractory green alloy. The density is measured by the Archimedes drainage method, ρ = 5.798g / cm 3 .

[0072] Figure 5 The scanning electron microscope microstructure of the high-strength, tough, lightweight, multi-component refractory green alloy of Example 2 was obtained after being kept at 850°C for 10 minutes and then immediately water quenched. It can be seen that after the cold rolling and annealing treatment, the alloy structure is dense, and the grains are relatively large and evenly distributed.

[0073] Figure 6 This is the corresponding XRD pattern of Example 2.

[0074] Figure 7 This is a homogeneous tensile engineering stress-engineering strain curve of the high-strength, toughness, lightweight multi-component refractory green alloy of Example 2. After vacuum annealing, the alloy exhibits a tensile yield strength of 942 MPa and a tensile elongation of 37.3%.

[0075] The obtained high-strength, tough, lightweight, multi-component refractory green alloy was further aged at a temperature of 350°C for 168 h, followed by immediate water quenching. Figure 8This is a graph showing the engineering stress-engineering strain curve of the high-strength, tough, lightweight, multi-component refractory green alloy after aging, and the strength and plasticity of the alloy are simultaneously improved.

[0076] Example 3

[0077] (1) Raw material pretreatment: The recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy were polished and ultrasonically cleaned at room temperature for 30 minutes to remove surface dirt and impurities, and finally placed in a drying oven for drying;

[0078] (2) Raw material ratio: According to the chemical formula Ti 53.60 Zr 17.14 Nb 20.68 Al 6.34 V 2.24 The molar percentage and mass percentage of (atomic percentage) are converted based on 100g of alloy, and the ingredients are prepared according to the recycled alloy mass ratio Ti6Al4V:Zr-2.5Nb:Nb-1Zr=45:25:30;

[0079] (3) Melting: according to the melting point, the raw materials weighed in step 2 are placed in a water-cooled copper crucible of a vacuum arc furnace in turn, and the vacuum is evacuated to 5×10-3Pa, and repeated three times; argon is filled to 0.05MPa as a protective atmosphere; before melting, the extra Ti ingot pre-placed in the furnace is melted for 2min to consume the residual oxygen and nitrogen in the melting furnace, the melting current is 340A, and the melting time is 180 seconds; start melting the alloy ingot, and melt it repeatedly for 8 times. The melting current is controlled at 400A. Each melting arc should last for 8min and be supplemented by electromagnetic stirring technology. The current frequency is 10Hz to ensure that the alloy is fully mixed;

[0080] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10mm in a vacuum arc furnace for remelting and forming. After the sample is cooled, the sample is taken out. The specific operations are as follows: vacuuming to 4×10-3Pa, repeated three times; filling argon to 0.04MPa as a protective atmosphere; before smelting, melt the extra Ti ingot pre-placed in the furnace, the smelting current is 340A, and the smelting time is 120 seconds; start smelting the alloy ingot, and smelt it repeatedly for 4 times. The smelting current is controlled at 400A, and the arc should last for 8 minutes each time;

[0081] (5) Cold rolling annealing: The cast alloy was cut into 10.00 mm thick strip-shaped samples, with a single-pass rolling reduction of 10% and a total rolling reduction of 90%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first evacuated to 1×10 -3Pa, and then filled with argon to maintain the pressure in the tube at 0.001MPa. After the sealing is completed, the sample is kept at 850℃ for 10min and then immediately quenched in water to obtain a high-strength, lightweight, multi-component refractory green alloy. The density is measured by the Archimedes drainage method, ρ = 5.675g / cm 3 .

[0082] Fig. 9 The high-strength, toughness, lightweight, multi-component refractory green alloy of Example 3 was cold rolled by 90%, kept at 850°C for 10 min, and then immediately water quenched to obtain a scanning electron microscope microstructure. It can be seen that after the cold rolling and annealing treatment, equiaxed crystals are evenly distributed.

[0083] Fig.10 This is the corresponding XRD pattern of Example 3.

[0084] Fig.11 This is a homogeneous tensile engineering stress-engineering strain curve of the high-strength and toughness lightweight multi-component refractory green alloy of Example 3. The alloy exhibits a tensile yield strength of 913 MPa and a room temperature tensile elongation of 37.3%.

[0085] The obtained high-strength, tough, lightweight, multi-component refractory green alloy was further aged at a temperature of 350°C for 168 h, followed by immediate water quenching. Fig.12 This is a tensile engineering stress-engineering strain curve of the high-strength and toughness lightweight multi-component refractory green alloy after aging in Example 3, and the strength of the alloy is significantly improved.

[0086] Example 4

[0087] (1) Raw material pretreatment: The recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy were polished and ultrasonically cleaned at room temperature for 30 minutes to remove surface dirt and impurities, and finally placed in a drying oven for drying;

[0088] (2) Raw material ratio: According to the chemical formula Ti 57.54 Zr 16.53 Nb 16.72 Al 6.81 V 2.40 The molar percentage and mass percentage of (atomic percentage) are converted based on 100g of alloy, and the ingredients are prepared according to the recycled alloy mass ratio Ti6Al4V:Zr-2.5Nb:Nb-1Zr=50:25:25;

[0089] (3) Melting: The raw materials weighed in step 2 were placed into a water-cooled copper crucible in a vacuum arc furnace in order of their melting points, and the vacuum was evacuated to 5 × 10 -3Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 2 minutes to consume the residual oxygen and nitrogen in the smelting furnace, the smelting current is 340A, and the smelting time is 180 seconds; start smelting the alloy ingot, smelting repeatedly 8 times, the smelting current is controlled at 400A, each smelting arc should last for 8 minutes and supplemented with electromagnetic stirring technology, the current frequency is 10Hz, to ensure that the alloy is fully mixed;

[0090] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10mm in a vacuum arc furnace for remelting and forming. After the sample is cooled, the sample is taken out. The specific operations are as follows: vacuuming to 4×10-3Pa, repeated three times; filling argon to 0.04MPa as a protective atmosphere; before smelting, melt the extra Ti ingot pre-placed in the furnace, the smelting current is 340A, and the smelting time is 120 seconds; start smelting the alloy ingot, and smelt it repeatedly for 4 times. The smelting current is controlled at 400A, and the arc should last for 8 minutes each time;

[0091] (5) Cold rolling annealing: The cast alloy was cut into 10.00 mm thick strip-shaped samples, with a single-pass rolling reduction of 10% and a total rolling reduction of 90%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first evacuated to 1×10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.001MPa. After the sealing is completed, the sample is kept at 850℃ for 10min and then immediately quenched in water to obtain a high-strength, lightweight, multi-component refractory green alloy. The density is measured by the Archimedes drainage method, ρ = 5.501g / cm 3 .

[0092] Fig.13 The high-strength, toughness, lightweight, multi-component refractory green alloy of Example 4 was cold rolled by 80%, kept at 850°C for 10 min, and then immediately water quenched to obtain a scanning electron microscope microstructure. It can be seen that after the cold rolling and annealing treatment, equiaxed crystals are evenly distributed.

[0093] Fig.14 This is the corresponding XRD pattern of Example 4.

[0094] Fig.15 This is a homogeneous tensile engineering stress-engineering strain curve of the high-strength, toughness, lightweight, multi-component refractory green alloy of Example 4. The alloy exhibits a tensile yield strength of 904 MPa and a room temperature tensile elongation of 38.4%.

[0095] The obtained high-strength, tough, lightweight, multi-component refractory green alloy was further aged at a temperature of 350°C for 168 h, followed by immediate water quenching. Fig.16This is a tensile engineering stress-engineering strain curve of the high-strength, toughness, lightweight, multi-component refractory green alloy of Example 4 after aging treatment, and the strength of the alloy is further improved.

[0096] Comparative Example 1

[0097] Ti6Al4V alloy

[0098] According to the literature Zhao R, Chen C, Shuai, Sansan Hu, Tao Fautrelle, Yves Liao, Hanlin Lu, Jian Wang, Jiang Ren, Zhongming. Enhanced mechanical properties of Ti6Al4V alloy fabricated by laser additive manufacturing under static magnetic field [J]. materials research letters, 2022, 10 (8): 530-538., it can be seen that the strength of Ti6Al4V alloy is relatively high at about 800 MPa, but the plasticity is relatively low at only 14%.

[0099] Comparative Example 2

[0100] Zr-2.5Nb alloy

[0101] According to the literature Rodriguez-Espinoza, BL, et al. "High-strength low-modulus biocompatible Nb-1Zr alloy processed by accumulative roll bonding." Materials Science & Engineering, A. Structural Materials: Properties, Misrostructure and Processing 797-(2020): 797., it can be seen that the strength of Zr-2.5Nb alloy is about 500MPa and the plasticity is about 20%.

[0102] Comparative Example 3

[0103] Nb-1Zr alloy

[0104] According to the document Yu T, Ye P, Chang Z. The Oxidization Behavior of Zr-2.5Nb (wt%) Alloy in Dry Air [J]. High Temperature Corrosion of Materials, 2023. DOI: 10.1007 / s11085-023-10149-3, the properties of Nb-1Zr alloys vary depending on the preparation method, heat treatment conditions, and added trace elements of the alloy. Generally speaking, the yield strength of Nb-1Zr alloys ranges from 250 to 450 MPa, and the elongation ranges from 10 to 30%.

[0105] Comparative Example 4

[0106] In this comparative example 4, based on Example 1, 100g of alloy was converted as the basis, and the recycled alloy mass ratio Ti6Al4V: Zr-2.5Nb: Nb-1Zr = 25:25:50 was used for batching. When the pressure in the vacuum arc furnace was pumped to 5×10 -3 After Pa, an inert gas is filled in, and under the protection of the inert gas, the alloy sample is turned over repeatedly and melted 6 times, and then cast to obtain a casting. The other conditions are the same as those in Example 1, that is, the alloy in Comparative Example 4 is obtained.

[0107] Fig.17 This is the macroscopic morphology of the comparative alloy after rolling. The alloy cracked during rolling deformation.

[0108] The present invention develops a multi-component refractory green alloy with high strength and toughness by recycling titanium alloy, niobium alloy and zirconium alloy. The room temperature tensile elongation reaches 40.0%, and the room temperature tensile yield strength is 800-1000 MPa. The alloy density is ρ=5.50-6.00 g / cm 3 Direct cold rolling-annealing treatment can be achieved at room temperature to achieve organizational control, which is beneficial to deformation processing and can realize the preparation of large-size samples; at the same time, it can simplify the cumbersome preparation process, reduce the preparation cost, effectively alleviate the problem of resource shortage to reduce production costs, reduce the exploitation of mineral resources to reduce environmental pollution.

[0109] The high-strength, tough, lightweight, multi-component refractory green alloy provided by the present invention has the following characteristics in terms of component matching: Compared with general multi-component alloys, the alloy uses recycled alloys instead of pure metal particles as raw materials, which can significantly reduce the cost of alloy preparation; at the same time, it reduces the pollution to the environment caused by refining pure metals, which is conducive to the development of green multi-component alloys. In terms of alloy performance, it has good strength-plasticity matching while achieving lightweight; the developed high-strength, tough, lightweight, multi-component refractory green alloy has high specific strength, low density, high oxidation resistance and good creep resistance, and can be used for heat-resistant components in aviation, aerospace, and automobile industries, and has excellent room temperature processing deformation ability, especially for the forming of complex-shaped thin-walled components, and can obtain precise and complex components with no or nearly no margin, greatly reducing metal loss, improving material utilization, reducing a large amount of machining, and greatly reducing production costs.

[0110] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A high-strength, light-weight, multi-component refractory green alloy, characterized by: The green alloy is obtained by smelting recycled titanium alloy, recycled niobium alloy and recycled zirconium alloy as raw materials, wherein, by weight percentage, the recycled titanium alloy is 28-55wt%, the recycled niobium alloy is 22-35wt%, and the recycled zirconium alloy is 22-38wt%. Among them, the recycled titanium alloy is Ti6Al4V alloy, the recycled niobium alloy is Nb-1Zr alloy, and the recycled zirconium alloy is Zr-2.5Nb alloy.

2. The high-strength, toughness, lightweight, multi-component refractory green alloy according to claim 1, characterized in that: The recycled titanium alloy includes Ti6Al4V alloy from waste oil drilling pipes, valves, pump bodies, eyeglass frames, bicycle frames, and mobile phone casings.

3. The high-strength, toughness, lightweight, multi-component refractory green alloy according to claim 1, characterized in that: The recycled niobium alloy includes Nb-1Zr alloy from waste high-temperature nozzles, waste nuclear reactor cladding materials, and waste surgical tools.

4. The high-strength, toughness, lightweight, multi-component refractory green alloy according to claim 1, characterized in that: The recycled zirconium alloy includes Zr-2.5Nb alloy derived from waste electronic device circuit board brackets, waste kitchen knives, waste nuclear reactor cladding materials, and waste nuclear industry materials.

5. The high-strength, toughness, lightweight, multi-component refractory green alloy according to any one of claims 1 to 4, characterized in that: The green alloy includes, by atomic percentage, 38.0-60.0 at% Ti, 14-28.0 at% Zr, 14.0-28.0 at% Nb, 4.0-8.0 at% Al, 1.0-4.0 at% V and trace elements Fe, Ta, W, Si, Ni, Mo and Cr, and the atomic percentage of each trace element is 0.01-2.0 at%.

6. The high-strength, toughness, lightweight, multi-component refractory green alloy according to claim 5, characterized in that: The high-strength, tough, lightweight, multi-component refractory green alloy has the following characteristics: (a) The density of the alloy is 5.30-6.00 g / cm 3 ; (b) Direct cold rolling-annealing treatment can be achieved at room temperature, with a cold rolling deformation of 20 to 100%; (c) The tensile yield strength of the high-strength, lightweight, multi-component refractory green alloy at room temperature is 800-1100 MPa ; (d) The tensile elongation of the high-strength, tough, lightweight, multi-component refractory green alloy at room temperature is above 30.0%.

7. The method for preparing a high-strength, tough, lightweight, multi-component refractory green alloy according to any one of claims 1 to 6, characterized in that: include, Recover titanium alloy, niobium alloy and zirconium alloy raw materials according to mass ratio; Use vacuum arc melting or vacuum induction melting; By cold rolling deformation and then annealing in vacuum or protective atmosphere, a high-strength, tough, lightweight, multi-component refractory green alloy is obtained.

8. The method for preparing the high-strength, tough, lightweight, multi-component refractory green alloy according to claim 7, characterized in that: The smelting is carried out in a vacuum or inert gas atmosphere; the vacuum degree of the smelting under vacuum is ≥1×10 -1 Pa; the smelting is carried out under an inert gas atmosphere, and the inert gas pressure in the smelting furnace is 0.000001~0.05MPa.

9. The method for preparing a high-strength, tough, lightweight, multi-component refractory green alloy according to claim 7 or 8, characterized in that: The cold rolling deformation is adopted, the rolling reduction in a single pass is ≤20%, and the total rolling reduction is 20% to 100%.

10. The method for preparing the high-strength, tough, lightweight, multi-component refractory green alloy according to claim 9, characterized in that: Annealing is performed in a vacuum or inert gas atmosphere at a temperature of 700 to 1250° C. for 5 to 60 minutes, followed by quenching. Further aging treatment may also be performed after annealing as required at a temperature of 100 to 600° C. for 0 to 800 hours, followed by quenching.

Citation Information

Patent Citations

  • Refractory high-entropy alloy material with high plasticity and low neutron absorption section and preparation method thereof

    CN112708817A

  • Ti-rich high-entropy alloy with high specific strength, high plasticity and high toughness and preparation of Ti-rich high-entropy alloy

    CN113652591A

  • Lightweight high-strength multi-component refractory alloy with ultrahigh room-temperature tensile ductility and preparation method of lightweight high-strength multi-component refractory alloy

    CN116497257A

  • High-strength and high-toughness TiZrNbV series high-entropy alloy with ordered oxygen complex and preparation method of high-strength and high-toughness TiZrNbV series high-entropy alloy

    CN116770150A

  • Method for preparing high-entropy alloy from niobium-tantalum waste

    CN117587284A